Evaluation of corporate income tax rates reduction policy applied to the general equilibrium approach and the degree of self-financing method: Case study in Indonesia - Ryan Mohammad; Helmi Zus Rizal (Directorate General of Taxes, 2023)
The reduction of the corporate income tax rate from 25% to 22% in 2020 is one of the Indonesian government's initiatives to hasten the country's economic recovery in response to the COVID-19 pandemic. In this paper, we aim to evaluate those policies’ impact on other tax revenue policies. According to our estimation using the General Equilibrium approach and the Degree of Self Financing (DSF) method, the measurement results demonstrate that nearly a quarter of 93,8% from the total lost tax revenue resulting from the policy of lowering the corporate income tax rate will be made up for by an increase in other tax revenues in the form of: 17.55 percent of individual income tax revenue, 5.94 percent of VAT, and 0.000197 percent of Tax on Deposits. However, given that only a quarter of 93,8% from the lost corporate income tax revenue will be recovered, the government's decision to keep the corporate income tax rate at 22 percent in 2022 and beyond is still reasonable.